HEALTH DISASTER PREVENTION: HYPERTENSION WITH ZINGERBER OFFICINALE AND CURCUMA LONGA - Asmarani, Fajarina Lathu; Muflih, Muflih (Universitas Respati Yogyakarta, 2021)
Hypertension is a risk factor for serious diseases. The country's loss due to the cost of this disease is quite a lot and the recovery time is long. Worker productivity due to hypertension becomes low and disrupts the economic function of the family. If it is not resolved, Health Disaster cannot be avoided. Zingerber Officinale and Curcuma Longa have been used traditionally to treat hypertension. The purpose of this study was to scientifically prove the effectiveness of Zingerber Officinale and Curcuma Longa on blood pressure in hypertensive patients. Fifty respondents were selected by Consecutive Sampling. Before the intervention, the respondents had their blood pressure measured. Respondents were given 200 mg of Zingerber Officinale and Curcuma Longa powder mixed into 200 ml of warm water to drink for seven days. After the intervention, respondents measured their blood pressure. Data were analyzed by Wilcoxon Test. After the intervention, systolic blood pressure decreases 10.8 mmHg from 162,4 mmHg to 151.6 mmHg. And diastolic blood pressure also decreases from 94.7 mmH to 88.3 mmHg. There was a significant difference (p = 0.000) between blood pressure (systolic and diastolic) before and after the intervention.